Pengaruh Etika Bisnis Islam dan Pemasaran Online Melalui Grabfood terhadap Peningkatan Omzet Usaha Kuliner di Kabupaten Magetan - Ayu Linjanari (Scimadly Publishing, 2024)
This research aims to find out how Islamic business ethics and online marketing through Grabfood influence the increase in culinary business turnover in Magetan Regency. This type of research is quantitative research using primary data. The data source for this research is a data collection method in the form of a questionnaire. Source of data comes from the results of the answers to the questionnaire. The data analysis methods used are classical assumption tests, multiple linear regression analysis, hypothesis testing (t test, F test and coefficient of determination). The population in this study were 65 businesses with a sample of 56 respondents. The research results show that Islamic business ethics has a significance value of 0.049 <0.05, meaning that Islamic business ethics influences increasing turnover. Online marketing has a significance value of 0.019 <0.05, meaning that online marketing via grabfood affects increased turnover.